Assessing Gender Dimorphism Indicators in Anthropometric Characteristics and Features of the Bony Pelvis of Female Representatives of Pair and Group Types in Sports Acrobatics - Bachynska, Nataliia Veronika; Doroshenko, Eduard; Svatiev, Andrii; Bohuslavskyi, Victor (Physical Education Theory and Methodology, 2025)
Objectives. The study aimed to examine individual anthropometric indicators, focusing on the bony pelvis size in female acrobats of various roles during the puberty and youth age, as well as in persons who do not engage in playing sports. Materials and methods. The sports qualifications of female acrobats were sub-elite and elite athletes. The study population comprised 32 athletes having appropriate positions — top, middle, and bottom: (12 female acrobats performing their roles at the top, 20 female acrobats performing their roles in the middle and at the bottom). Girls of the same age categories (12-15 and 16-23 years old) who did not engage in playing sports (control group 1 and 2) also took part in the study. The research methods employed included the measurements of body length (cm), body weight (kg), shoulder width (cm), determination of body mass index (conventional unit); pelvimetry was performed to detect the transverse and longitudinal dimensions of the bony pelvis, as well as the degree of maturity of the pelvic bones using the index of pelvic bone (IPB). The methods of mathematical statistics were used to gain a comprehensive understanding of the data. Results. A comparative analysis was conducted to identify the differences between female acrobats aged 12-15 years old and performing their roles at the top, female acrobats aged 16-23 years old and performing their roles in the middle and at the bottom, and control groups of the same age categories. The analysis revealed the presence of changes in morphofunctional indicators of the bony pelvis below the normative values during the study. Conclusions. Morphological criteria of sexual dimorphism were found in female acrobats, namely: in the indicators of shoulder width and bony pelvis. These processes can be regarded as adaptive, occurring under the influence of physical and psychological training, as well as competitive loads of high intensity.